2002
DOI: 10.1590/s0100-84042002000300008
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura fitossociológica da comunidade de lianas em uma floresta estacional semidecidual na Fazenda Canchim, São Carlos, SP

Abstract: -(Phytosociological structure of a liana community in a seasonal semideciduous forest at Fazenda Canchim, São Carlos, SP). A phytosociological research concerning liana vegetation has been accomplished at Fazenda CanchimEmbrapa/CPPSE. The forest under analysis, which is fragmented in two parts, covers an area of 112 ha, located at 21º57' S and 47º50'W. 75 plots of 10 × 10 m were studied where all liana individuals had at least 2.5 cm in diameter, measured 1.3 m above soil level. Five hundred and twenty eight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
55

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 10 publications
2
23
1
55
Order By: Relevance
“…As 10 famílias mais freqüentes na gleba Maravilha, entre as que apresentam espécies de lianas, totalizaram 75,8% das espécies encontradas e correspondem a apenas 33,3% das famílias estudadas, demonstrando que apesar do elevado número de espécies de lianas estas concentram-se em poucas famílias, reafirmando os estudos de Gentry (1991), Hora & Soares (2002), R.G. Udulutsch (dados não publicados) e Udulutsch et al (2004).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…As 10 famílias mais freqüentes na gleba Maravilha, entre as que apresentam espécies de lianas, totalizaram 75,8% das espécies encontradas e correspondem a apenas 33,3% das famílias estudadas, demonstrando que apesar do elevado número de espécies de lianas estas concentram-se em poucas famílias, reafirmando os estudos de Gentry (1991), Hora & Soares (2002), R.G. Udulutsch (dados não publicados) e Udulutsch et al (2004).…”
Section: Resultsunclassified
“…Gentry (1976) analisou a distribuição de espécies pertencentes à família Bignoniaceae em diversos ecossistemas na América Central, notando que em todos eles a média de espécies encontradas foi em torno de 20 espécies, incluindo arbóreas e lianas. O número de espécies desta família encontrado em nosso estudo e nos demais no interior paulista aqui analisados, com exceção de Rezende & Ranga (2005) que encontrou 13 espécies, foi igual ou maior, mesmo restringindo-se às espécies arbóreas e arbustivas (Morellato & Leitão Filho 1996;Hora & Soares 2002; R.G. Udulutsch, dados não publicados; Udulustch et al 2004), alcançando 29 espécies em um mesmo fragmento.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Given these apparent advantages, Villagra & Romaniuc-Neto (2010) showed that even a small vegetation fragment, such as that evaluated in Itaberá, can harbor the same vine species richness as do large areas of contiguous forest. Therefore, the fragmented landscape is a factor that stimulates the presence of vines, not only at the edges, as described by different authors (Hora & Soares 2002;Benítez-Malvido & Martínez-Ramos 2003), but also in the forest interior. The fragment of Araucaria forest in Itaberá also features an extensive edge effect, with an abundance of bamboo-like plants, largely on the perimeter, where the study area borders agricultural land.…”
Section: Discussionmentioning
confidence: 96%